2008
DOI: 10.1007/s00425-008-0847-5
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of theobromine synthase genes in purine alkaloid-free species of Camellia plants

Abstract: Caffeine (1,3,7-trimethylxanthine) and theobromine (3,7-dimethylxanthine) are purine alkaloids that are present in high concentrations in plants of some species of Camellia. However, most members of the genus Camellia contain no purine alkaloids. Tracer experiments using [8-(14)C]adenine and [8-(14)C]theobromine showed that the purine alkaloid pathway is not fully functional in leaves of purine alkaloid-free species. In five species of purine alkaloid-free Camellia plants, sufficient evidence was obtained to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 36 publications
0
11
0
1
Order By: Relevance
“…This involved designing degenerated primers based on conserved regions in tea caffeine synthase (AB031280) and unknown proteins of Arabidopsis thaliana. The evolutionary relationship of caffeine synthase family enzymes has been summarized elsewhere (Ashihara, Kato, et al, 2011;Ishida et al, 2009). Comparisons of the amino acid sequences of the caffeine synthase family in Coffea and Camellia plants have been reported.…”
Section: Genes and Molecular Structure Of N-methyltransferasesmentioning
confidence: 99%
See 1 more Smart Citation
“…This involved designing degenerated primers based on conserved regions in tea caffeine synthase (AB031280) and unknown proteins of Arabidopsis thaliana. The evolutionary relationship of caffeine synthase family enzymes has been summarized elsewhere (Ashihara, Kato, et al, 2011;Ishida et al, 2009). Comparisons of the amino acid sequences of the caffeine synthase family in Coffea and Camellia plants have been reported.…”
Section: Genes and Molecular Structure Of N-methyltransferasesmentioning
confidence: 99%
“…Consumption of purine alkaloids can have a diversity of impacts on human health (Lean, Ashihara, Clifford, & Crozier, 2012). In this context, the occurrence of theobromine synthase genes in apparently non-purine alkaloid accumulating species of Camellia, such as C. japonica and C. kissii (Table 4.2; Ishida, Kitao, Mizuno, Tanikawa, & Kato, 2009), is of interest. as a consequence the distribution of purine alkaloids is restricted to species in six families of higher plants.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was no group formed exclusively by caffeine synthase or theobromine synthase. These two enzymes seem to share the same phylogenetic profile, which was also observed in several studies (Uefuji et al, 2003;Yoneyama et al, 2006;McCarthy and McCarthy, 2007;Ângelo et al, 2008;Freitas, 2009;Ishida et al, 2009).…”
Section: Complete Coding Sequence Of N-methyltransferasementioning
confidence: 51%
“…The analysis of orthologous genes of TCS1 in Camellia plants is indispensable for clarifying which of the two synthases is ancestral-caffeine or theobromine synthase. Ishida et al demonstrated the occurrence of theobromine synthase gene in purine alkaloid-free species derived from Camellia plants that belonged to the sub-genera Protocamellia, Camellia, and Metacamellia [17]. This observation strongly suggested that caffeine synthase has evolved from theobromine synthase in Camellia plants.…”
Section: Caffeine Synthase and Theobrominesynthase From Theaceaementioning
confidence: 99%